CAP reform and its implications for developing countries: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
This Executive Brief presents the 2012-13 state of play of the CAP reform, focusing mainly on the implications for developing countries and, in particular, ACP countries. Besides examining the main production and trade effects of the CAP implementation, the Brief presents some features of the EU’s CAP that can serve as lessons to follow for ACP policy makers. These are: the use of traditional agricultural trade policy tools in support of agro-food sector development; the design and utilisation of new policy tools to strengthen the functioning of agro-food supply chains, in order to consolidate and expand the agricultural basis of production; and the design and implementation of measures to insulate domestic producers from the adverse effects of price instability in an era of rising input costs.